2012
DOI: 10.3109/01612840.2011.630497
|View full text |Cite
|
Sign up to set email alerts
|

A Causal Model of Depression Among Older Adults in Chon Buri Province, Thailand

Abstract: The purposes of this study are to develop and empirically test a theoretical model that examines the relationships between a set of predictors and depression among older adults. A biopsychosocial model was tested with 317 community dwelling older adults residing in Chon Buri Province, Thailand. A face-to-face interview was used in a cross-sectional community-based survey. A hypothesized model of depression was tested by using path analysis. It was found that the modified model fitted the data and the predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Indeed, females are distressed by network relationships, but males are affected by job or financial problems, both of which lead to depression (19). Illnesses, functional impairment, and perceived deteriorating health are also highly correlated with depression (5,6,9,19,27,28). Chronic illnesses, that leads to functional decline, can be regarded as a risk factor for depression (30).…”
Section: Risk Factors For Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, females are distressed by network relationships, but males are affected by job or financial problems, both of which lead to depression (19). Illnesses, functional impairment, and perceived deteriorating health are also highly correlated with depression (5,6,9,19,27,28). Chronic illnesses, that leads to functional decline, can be regarded as a risk factor for depression (30).…”
Section: Risk Factors For Depressionmentioning
confidence: 99%
“…However, when facing widowhood, older women are less vulnerable than older men (34). Stressful life events are still risk factors for depression and are predictors of the onset and relapse of depression (5,6,15,19,28,(35)(36)(37). However, previous research has covered many risk factors related to depression but only partly underlined the association between stressful life events and depression (20).…”
Section: Risk Factors For Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some studies (Piboon et al, 2012) mentioned that getting old, being female, health status, greater number of chronic illnesses or, functional status such as Activities of Daily Living (Jitaree, 2555), social support, grief and loss experience were associated with depression. Some previous studies demonstrated the issues and problems of depression in nursing homes located in many cities in Thailand such as Bangkok (Somporn, 2011), Chiang Mai (Suwattanakoop, 2013;Wongpakaran & Wongpakaran, 2012) and Nakhonratchasima (Satra, 1988).…”
Section: Factors Related To Depression Among Older People Living In Hmentioning
confidence: 99%
“…Consequently, suicide may impact them later (Bolger, 2005). Risk factors which are the leading causes of late life depression are physical impairment or comorbidity (such as chronic illnesses, pain) (Piboon, Subgranon, Hengudomsub, Wongnam, & Louise Callen, 2012), bereavement, adverse life events, loneliness, and social isolation (Bolger, 2005).…”
Section: Factors Related To Depression Among Older People Living In Hmentioning
confidence: 99%